A DELPHI TECHNIQUE APPROACH TOWARDS THE NEED FOR AND RELEVANCE OF CONSTRUCTION PROJECT MONITORING AND EVALUATION PRACTICES - Callistus TENGAN; Clinton AIGVABOA (Journal of Construction Project Management and Innovation)
The practical experience of the researchers on the implementation of the inductive methodology to knowledge dissemination using the Delphi technique approach is reported in this study. The Delphi method is a vital procedure of reaching consensus on issues that cannot be resolved in a once-off discussion. The research commenced with five questions to ascertain the views of experts with the aim of reaching consensus on the need for and relevance of monitoring and evaluation (M&E) implementation in achieving project success in Ghana’s construction industry. Experts for the study were identified from the Ghanaian construction industry (quantity surveyors, architect, and engineers), research, and academic institutions of higher learning faculties in Ghana. After two iterative Delphi rounds, consensus was achieved on the need for and relevance of M&E to achieve project success as suggested by the experts during the Delphi process. Based on the difficulties faced in the process, the study recommends clear and concise instructions to Delphi experts on the process. Also, the length of the structured Delphi questionnaire should be as short as possible to ensure a high response rate with a constant reminder to experts before the close of the submission of responses. In conclusion, the authors argue that the Delphi technique is vital for studies in areas where consensus on the need for and relevance of construction project management practices is yet to be reached.